2017
DOI: 10.2183/pjab.93.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural biology of protein lysine deacetylases

Abstract: Histone acetylation is a reversible posttranslational modification that plays a fundamental role in regulating eukaryotic gene expression and chromatin structure/function. Key enzymes for removing acetyl groups from histones are metal (zinc)-dependent and NAD+-dependent histone deacetylases (HDACs). The molecular function of HDACs have been extensively characterized by various approaches including chemical, molecular, and structural biology, which demonstrated that HDACs regulate cell proliferation, differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 183 publications
(200 reference statements)
1
52
0
Order By: Relevance
“…Since protein acylation is regulated by metabolites, such as acyl-CoA and NAD + , this modification could play a role in the regulation of protein function in response to nutrient signals and/or metabolism. [1][2][3][4] Corynebacterium glutamicum is an excellent glutamate producer that is utilized for industrial production of amino acids including L-glutamate and L-lysine. 5) We reported that the acetylation and succinylation profiles of many enzymes are drastically changed in response to L-glutamate overproduction in C. glutamicum, including enzymes involved in central metabolic pathways.…”
mentioning
confidence: 99%
“…Since protein acylation is regulated by metabolites, such as acyl-CoA and NAD + , this modification could play a role in the regulation of protein function in response to nutrient signals and/or metabolism. [1][2][3][4] Corynebacterium glutamicum is an excellent glutamate producer that is utilized for industrial production of amino acids including L-glutamate and L-lysine. 5) We reported that the acetylation and succinylation profiles of many enzymes are drastically changed in response to L-glutamate overproduction in C. glutamicum, including enzymes involved in central metabolic pathways.…”
mentioning
confidence: 99%
“…The first HDAC6 inhibitor to be investigated was the natural compound trichostatin (TSA) [ 323 , 324 ]. It is a non selective HDAC inhibitor that acts by binding to the zinc ion at the HDAC active site of most zinc-dependent HDACs, including HDAC6 [ 325 ]. Its in vitro supplementation has been reported to lead to the hyperacetylation of tubulin in mammalian cells [ 324 ].…”
Section: Microtubule-targeting Agentsmentioning
confidence: 99%
“…Here, we focus on the second family, which consists of 11 metal‐dependent KDACs in human cells. These enzymes all share a highly conserved catalytic domain (Figure 2) and utilize a divalent transition metal cation in the active site to promote hydrolysis, resulting in the removal of the acetate from lysine side chains 9,14,15 . The identity of the transition metal is usually Zn 2+ in vitro, but evidence exists that some KDACs may utilize Fe 2+ in vivo 14,16 .…”
Section: Lysine Deacetylasesmentioning
confidence: 99%